Behind palace doors marriage and divorce in the house of Windsor - Dempster, Nigel 1941-2007; Evans, Peter (Putnam's, 1993)
A through-the-keyhole story of the marital woes of the Windsors and their most celebrated members, Prince Charles and Princess Diana.
Keywords: Elizabeth <II, Queen of Great Britain, 1926-> -- Family; Windsor, House of; Windsor -- Familie; Geschichte 1900-2000; Geschichte; Divorce -- Great Britain -- History -- 20th century; Marriages of royalty and nobility -- Great Britain -- History -- 20th century; Monarchy -- Great Britain -- History -- 20th century; Princes -- Great Britain -- Biography; Princesses -- Great Britain -- Biography; Queens -- Great Britain -- Biography; Skandal; Großbritannien; Biografie -- 1900-1993